2018
DOI: 10.3390/molecules23112820
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Shikonin Derivatives and Pharmacological Effects of Cyclopropylacetylshikonin on Melanoma Cells

Abstract: Despite much research in the last centuries, treatment of malignant melanoma is still challenging because of its mostly unnoticeable metastatic spreading and aggressive growth rate. Therefore, the discovery of novel drug leads is an important goal. In a previous study, we have isolated several shikonin derivatives from the roots of Onosma paniculata Bureau & Franchet (Boraginaceae) which evolved as promising anticancer candidates. β,β-Dimethylacrylshikonin (1) was the most cytotoxic derivative and exhibited st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…The present study identified that a high concentration of shikonin demonstrated characteristics of necrosis, whereas a low concentration demonstrated characteristics of apoptosis (data not shown). In spite of the large number of studies indicating that shikonin induces apoptosis in various human tumor cell lines (8,9,11), the molecular mechanism of the potential anti-glioma effect of shikonin is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified that a high concentration of shikonin demonstrated characteristics of necrosis, whereas a low concentration demonstrated characteristics of apoptosis (data not shown). In spite of the large number of studies indicating that shikonin induces apoptosis in various human tumor cell lines (8,9,11), the molecular mechanism of the potential anti-glioma effect of shikonin is not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it inhibits cell proliferation and migration, and induces cell cycle arrest and apoptosis in murine melanoma B16F0 cells [626]. Another novel shikonin derivative, cyclopropylacetylshikonin, exhibits strong anti-tumor and pro-apoptotic effects in human melanoma WM164 and MUG-MEL2 cells [628]. In addition, drug delivery system is also developed to promote the intracellular delivery of shikonin.…”
Section: Shikoninmentioning
confidence: 99%
“…In addition, cyclopropylacetylshikonin, a structural analogue of acetylshikonin, suppressed the proliferation of melanoma cell lines (WM164 and MUG-Mel2). The mechanisms were associated with inducing caspase-dependent apoptosis, leading to doublestranded DNA breaks, and increasing the protein levels of cleaved Poly ADP-ribose polymerase (Durchschein et al 2018).…”
Section: Lung Cancermentioning
confidence: 99%
“…The mechanisms were associated with inducing caspase-dependent apoptosis, leading to double-stranded DNA breaks, and increasing the protein levels of cleaved Poly ADP-ribose polymerase (Durchschein et al. 2018 ).…”
Section: Pharmacologymentioning
confidence: 99%